1999
DOI: 10.1164/ajrccm.159.2.9711068
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Airway Inflammation but Accommodated Antioxidant and Lung Function Responses after Repeated Daily Exposure to Nitrogen Dioxide

Abstract: Nitrogen dioxide (NO2) is a common indoor and outdoor air pollutant that may induce deterioration of respiratory health. In this study the effects of repeated daily exposure to NO2 on airway antioxidant status, inflammatory cell and mediator responses, and lung function were examined. Healthy nonsmoking subjects were exposed under controlled conditions to air (once) and to 2 ppm of NO2 for 4 h on four consecutive days. Lung function measurements were made before and immediately after the end of each exposure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 31 publications
5
56
0
2
Order By: Relevance
“…In addition, the presence of indoor pollutants, even at low concentrations, may have an important biological impact because of long periods of exposure. This is much more than the four peaks reported in experimental study (36). In this real situation, more than producing a chronic and silent inflammatory process, NO 2 and the other pollutants can really be harmful, producing chronic damage to the respiratory system.…”
Section: Modelmentioning
confidence: 76%
See 1 more Smart Citation
“…In addition, the presence of indoor pollutants, even at low concentrations, may have an important biological impact because of long periods of exposure. This is much more than the four peaks reported in experimental study (36). In this real situation, more than producing a chronic and silent inflammatory process, NO 2 and the other pollutants can really be harmful, producing chronic damage to the respiratory system.…”
Section: Modelmentioning
confidence: 76%
“…Frampton et al (35) found an inflammatory response that persisted at least 18 h after exposure, while Blomberg et al (36) demonstrated major decrements in FEV 1 just after exposure and this lung function indicator response was attenuated after repeated exposures, even in the presence of a persistent neutrophilic inflammation in the airways. They concluded that NO 2 is a proinflammatory air pollutant under conditions of repeated exposure.…”
Section: Modelmentioning
confidence: 99%
“…Four experimental studies of mild atopic asthmatic adults have shown an enhancement of airway responses to allergens after exposure to 260-400 ppb NO 2 (30)(31)(32)(33). There is also some evidence that NO 2 exposure leads to persistent neutrophilic infiltration in human airways (34) and to increased histamine release in histocultured human nasal mucosa (35). The inflammatory mechanisms of pollen and fungal allergens in allergic respiratory disease have also been described (36)(37)(38).…”
Section: Discussionmentioning
confidence: 98%
“…Healthy subjects have been exposed acutely to NO 2 concentrations that range from 0.3 ppm to 2.0 ppm (1-4 hours); sensitive subgroups, including asthmatics and chronic obstructive pulmonary disease patients have been exposed to 0.26-1.00 ppm. Above 1 ppm, clear evidence of inflammation has been observed in healthy subjects in a number of studies (Helleday et al, 1995;Devlin et al, 1999;Pathmanathan et al, 2003;Blomberg et al, 1999), but the picture is less established at concentrations between 0.2 ppm and 1.0 ppm (Vagaggini et al, 1996;Jörres et al, 1995;Gong et al, 2005;Frampton et al, 2002;Riedl et al, 2012), partially because of inconsistent responses in the varying end-points examined.…”
Section: Chamber Studiesmentioning
confidence: 99%